Republic of Poland : Technical Assistance Report-Tax Administration-Modernization Challenges and Strategic Priorities. (IMF Staff Country Reports; Country Report ;, 2015)
This Technical Assistance Report provides advice on the modernization of the tax administration in Poland. Tax collections in Poland as a percentage of GDP are lower than those found in larger European Union member states. The report discusses collection performance of the main taxes in recent years and the approach to tax administration modernization. It also addresses selected issues concerning the tax administration institutional reform; the administration and delivery of core tax administration operations, including for the largest taxpayers; and the approach to managing compliance risks to the tax system.